(untitled) (Research, Society and Development, 2022)
Aims: This literature review aims to investigate the effect of probiotic supplementation on glucose metabolism and inflammatory biomarkers in pregnant women with gestational diabetes mellitus. Methods: Data were collected using the National Library of Medicine (Medline), Latin American & Caribbean Health Sciences Literature (Lilacs), Virtual Health Library (BVS) and Scientific Electronic Library Online (Scielo) databases. The following descriptors were used: “gestational diabetes”, “probiotic” and “inflammation”. Results: The main findings emphasized the improvement in fasting glucose and insulin resistance and a lesser impact on the improvement of inflammatory markers after probiotic supplementation in pregnant women diagnosed with gestational diabetes mellitus. Conclusions: The use of probiotics in pregnant women with gestational diabetes mellitus has shown positive actions to control glucose metabolism and proinflammatory factors, which may improve serum glucose levels, insulin sensitivity and inflammation.